OPTICAL COHERENCE TOMOGRAPHY 2: Diagnostic Tool to Study Peripheral Vitreoretinal Pathologies. Issue 2 (February 2019) - Cereda, Matteo G.; Corvi, Federico; Cozzi, Mariano; Pellegrini, Marco; Staurenghi, Giovanni
Abstract : Purpose: To investigate the utility of new wide-field optical coherence tomography (OCT) device in the evaluation of mid and far retinal periphery and to show its feasibility and advantages in clinical practice. Methods: Consecutive patients underwent a complete ophthalmologic examination including standard OCT and new prototype OCT2 derived from Heidelberg Spectralis. Results: Thirty-one eyes of 31 patients were studied with a total of 44 lesions, including 18 retinal detachments, 15 retinal holes and tears, 9 retinoschisis, and 2 retinal tufts. Fourteen (32%) lesions were found in mid and 30 (68%) in far periphery with 9 (20%) lesions in the superior region, 10 (23%) in the superior temporal, 8 (18%) in the temporal, 4 (9%) in the inferior temporal, 7 (16%) in the inferior, 4 (9%) in the nasal, and 2 (5%) in the superior nasal. Among the lesions evaluated by OCT2, 10 (71%) in mid periphery and 11 (37%) in far periphery could be imaged by standard OCT. Conclusion: The introduction of OCT2 into clinical practice may provide significant benefits for imaging peripheral retinal disorders. The application of OCT2 technology with 55° lens and scan length and angle modulation could improve our understanding of peripheral vitreoretinal disorders and facilitate their management. Abstract : The authors evaluated the ability of new wide-field optical coherence tomography to evaluate patients with peripheral vitreoretinal pathology. The authors found that optical coherence tomography 2 provides significant benefits for imaging of peripheral retinal disorders also allowing for high-resolution imaging of vitreoretinal interface, retina, and choroid with impact on both clinical and surgical care.